2007
DOI: 10.1111/j.1532-7078.2007.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Infants Show Distinct Negative Facial Expressions for Fear and Anger? Emotional Expression in 11‐Month‐Old European American, Chinese, and Japanese Infants

Abstract: Do infants show distinct negative facial expressions for different negative emotions? To address this question, European American, Chinese, and Japanese 11‐month‐olds were videotaped during procedures designed to elicit mild anger or frustration and fear. Facial behavior was coded using Baby FACS, an anatomically based scoring system. Infants' nonfacial behavior differed across procedures, suggesting that the target emotions were successfully elicited. However evidence for distinct emotion‐specific facial conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 39 publications
(49 reference statements)
7
47
0
1
Order By: Relevance
“…As indicated earlier, while DET describes distinct facial expressions for each discrete negative emotion, there is little evidence that during the first year these expressions are differentially distributed across situations in which different negative emotions are being induced. For example, Camras et al (2007) found that 11-month-old Chinese, Japanese, and American infants produced similar facial expressions in response to both nonpainful arm restraint and presentation of a disembodied toy gorilla head.…”
Section: Expressive Behavior and Action Tendenciesmentioning
confidence: 99%
“…As indicated earlier, while DET describes distinct facial expressions for each discrete negative emotion, there is little evidence that during the first year these expressions are differentially distributed across situations in which different negative emotions are being induced. For example, Camras et al (2007) found that 11-month-old Chinese, Japanese, and American infants produced similar facial expressions in response to both nonpainful arm restraint and presentation of a disembodied toy gorilla head.…”
Section: Expressive Behavior and Action Tendenciesmentioning
confidence: 99%
“…Psychophysiological approaches that have been productive in developmental research on children's responses to other types of stimuli (Fox, Schmidt, Henderson, & Marshall, 2007;Jones & Gagnon, 2007) may be especially appealing for their potential to unlock meaning in quantitative and qualitative differences in presentations of jealousy, and, more generally, toward illuminating an intrapersonal experience that is too multifaceted to be articulated by the young child. Thus, psychophysiological measures offer potential to shed light on the significance of affect expressions that are atypical, on affective displays that are lacking in expressivity, and possibly on discrete emotions, such as love, where affective experiences do not correspond in one-to-one fashion with any known facial expression (Aviezer et al, 2008;Barrett, Mesquita, Ochsner, & Gross, 2007;Camras et al, 2007;Camras & Shutter, under review;Eysenck, 1967;Field, 1996). Based on our observations of wide individual differences in the presentation of nascent jealousy, as well as the exquisite sensitivity and sheer intensity of what appears as raw passion in some infants, we would hazard to predict that efforts to unravel the socialization of jealousy and to comprehend conditions under which it goes awry will not be fully productive without deeper insight into the ''physiological fire'' that is jealousy's constitutional foundation.…”
Section: Jealousy As a Dimension Of Temperamentmentioning
confidence: 99%
“…Since the introduction of empirical methods for studying facial expression, there has been ongoing discussion about the relation of infants’ expressions to state and to emotional development more broadly; see for example (Camras et al, 2007; Camras, Sullivan, & Michel, 1993; Izard, 2007a). In the emotion literature, there is some consensus that emotions may be best conceptualized as processes or dimensions rather than states (Barrett, Mesquita, Ochsner, & Gross, 2007).…”
mentioning
confidence: 99%
“…An A/W model provides a coherent framework for understanding infant emotional behavior and development in contrast to extant models including facial expression. Differential Emotions Theory--DET (Izard, 2007a) and Dynamical Systems Theory--DST (Camras & Fatani, 2008; Camras et al, 2007) offer opposing theories of infant expression but have little to say about emotion processes relative to expression and behavior. A/W offers a third model.…”
mentioning
confidence: 99%
See 1 more Smart Citation